Testing an Online, Theory-Based Intervention to Reduce Pre-drinking Alcohol Consumption and Alcohol-Related Harm in Undergraduates: a Randomized Controlled Trial - Caudwell, K.; Mullan, Barbara; Hagger, Martin (Springer New York LLC, 2018)
Purpose: The present study tested the efficacy of a theory-based online intervention comprising motivational (autonomy support) and volitional (implementation intention) components to reduce pre-drinking alcohol consumption and alcohol-related harm. Method: Undergraduate students (N = 202) completed self-report measures of constructs from psychological theories, pre-drinking alcohol consumption, and alcohol-related harm at baseline and were randomly assigned to one of four intervention conditions in a 2 (autonomy support: present/absent) × 2 (implementation intention: present/absent) design. Participants completed follow-up measures of all variables at 4 weeks post-intervention. All participants received national guidelines on alcohol consumption and an e-mail summary of intervention content at its conclusion. Participants also received weekly SMS messages in the 4-week post-intervention period restating content relevant to their intervention condition. Results: Neither statistically significant main effect for either the autonomy support or implementation intention intervention components nor an interaction effect was found on the outcome measures. However, statistically significant reductions in pre-drinking alcohol consumption and alcohol-related harm were observed across all groups at follow-up, when compared to baseline. Conclusion: Reductions in outcome measures were likely related to elements common to each condition (i.e., provision of national guidelines, assessment of outcome measures, e-mail summary, and SMS messages), rather than motivational and volitional components.